DIVORCE TRENDS IN INDIA - Dr. Hiranmaya Nanda , Maithili Chaudhury (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Divorce and separation in India are viewed as fairly rare events and available information on the issue has been identified as quantitative gossip. Though there is a lack of quantitative evidence, India contains rich interdisciplinary literature on specific aspects of marital stability. This paper builds on this discourse in order to first contextualize the main facets of marriage and the socio cultural and legal structures affecting marriage longevity in India. Following this, the paper uses evidence from a broad nationally representative to present projections of incidence, patterns and differences of divorce and separation. Ultimately, using employment as a specific indicator, the paper explores the effect of social improvements between 1987 and 2015 on the longevity of partnerships. The findings show an upward trend and major differences in divorce and separation among children by country, ethnicity, rural and number and age. The results suggest that higher-educated marriage is more stable, and that the gap between higher-educated and lower-educated women has risen over time.